MANAGEMENT OF REGIONAL PROPERTY (BMD) AT PAMBALAH BATUNG REGIONAL GENERAL HOSPITAL, AMUNTAI, NORTH HULU SUNGAI REGENCY, SOUTH KALIMANTAN PROVINCE - Achmad Supranotho; Reno Affrian (PT. Antis International Publisher, 2026)
Objective: This study aims to analyze the management of Regional Property at Pambalah Batung Amuntai Hospital from the aspects of planning, procurement, use, utilization, security, maintenance, administration, and supervision. Method: The research uses a qualitative approach with data collection methods including in-depth interviews, observation, and document study. Data analysis is conducted descriptively and analytically. Results: The research findings indicate that the management of BMD at the Pambalah Batung Regional General Hospital in Amuntai has been implemented in accordance with the regulatory framework, but is not yet fully optimal due to limitations in human resources, underutilization of the asset information system, and weak internal supervision and control. Novelty: This research highlights the gaps in human resource capacity, information system utilization, and internal oversight in regional hospital asset management, providing recommendations to strengthen asset management, improve system integration, and enhance oversight to support hospital accountability and service quality.